Development of knowledge in Research and Development and its registry from patents in Brazil - a professional experience (Research, Society and Development, 2017)
This work seeks to provide a detail on the process of search of knowledge, starting from a basic tool that is the information. Knowledge in Research and Development work can be structured for the development of new technologies, products or processes, where knowledge can be registered through patents. Since it is necessary to know the legislation of the country of deposit, we will deal more specifically with the Brazilian patent system called the National Institute of Intellectual Property - INPI. The reflections presented come from a professional experience.